Efficacy and Safety of New Orodispersible Tablet Formulations of Praziquantel (Racemate and L-Praziquantel) in Schistosoma mansoni-Infected Preschool-Age Children and Infants: A Randomized Dose-Finding Phase 2 Study - N’Goran, Eliézer K.; Yalkinoglu, Özkan; Kourany-Lefoll, Elly; Tappert, Aliona; Hayward, Brooke; Yin, Xiaoyan; Bezuidenhout, Deon; Huber, Eric; Aka, N. A. David; Ouattara, Mamadou; Bagchus, Wilhelmina (Frontiers in Tropical Diseases, 2021)
Introduction Two novel formulations of praziquantel (PZQ) and Levo-(L-)PZQ (arpraziquantel) have been developed for the treatment of schistosomiasis in preschool-age children and infants. Methods This open-label, dose-finding Phase 2 study assessed the efficacy and safety of PZQ formulations in children and infants infected with Schisostoma mansoni in Côte d’Ivoire. In Part 1, 420 children aged 2.1–6.9 years (weight 10.0–29.9 kg) were enrolled and randomized to one of 7 treatment arms (n=60 per arm): commercially available racemate (rac)-PZQ at 3x20 mg/kg or 40 mg/kg (treatment arms 1 and 2); rac-PZQ orodispersible tablet (ODT) at 40 mg/kg or 60 mg/kg (treatment arms 3 and 4); or L-PZQ ODT at 30 mg/kg, 45 mg/kg, or 60 mg/kg (treatment arms 5, 6, and 7). The optimal formulation and dose identified (L-PZQ ODT 50 mg/kg) was used in Part 2, which enrolled 24 infants aged 6–24 months (weight 7.5–14.8 kg). Infants were treated in an age-staggered approach: age 13–24 months (treatment arm 8, n=20) and age 6–12 months (treatment arm 9, n=4). The primary endpoint was clinical cure rate (CR) demonstrated by the Kato–Katz method 14–21 days post-treatment. Secondary endpoints included CR by point-of-care circulating cathodic antigen, egg reduction rate (ERR), and adverse events (AEs). Results In Part 1, CRs ≥70% were achieved in all treatment arms and were highest with L-PZQ ODT 60 mg/kg (89.7%), rac-PZQ 3x20 mg/kg (89.5%), and L-PZQ ODT 45 mg/kg (86.0%). In Part 2, CRs were >90%. All treatment arms had ERRs >95%. Treatment-related AEs were reported by 71 participants (16.0%) and were similar across treatment arms; most were mild and transient. The most common treatment-emergent AEs were laboratory abnormalities. No deaths or discontinuation due to treatment-emergent AEs were reported and no new safety concerns were identified. Conclusion New rac-PZQ and L-PZQ ODT formulations used as single-dose therapy against S. mansoni demonstrated acceptable overall efficacy and safety in preschool-age children and infants, warranting further studies in this population. Clinical Trial Registration ClinicalTrials.gov, identifier NCT02806232; Pan African Clinical Trials Registry, identifier PACTR201604001493593.